Sociological Foundation of Islamic Banking Law Legislation as The Legal Umbrella of Economic and Islamic Finance Development in Indonesia - Abdul Ghafur (Institute for Research and Community Empowerment (LPPM TAZKIA), 2015)
Objective - Sociologically, the existence of Law No.21/2008 on Islamic Banking in the splendor of economic development and Islamic finance is an interesting thing to observe. This paper wants to discuss the sociological foundation of Islamic banking law legislation as the legal umbrella of economic and Islamic finance development in Indonesia.Methods – qualitative Research, includes the study of law.Conclusions – At least, there are several spectrums that can be understood from the emergence of this law. First,the establishment of Islamic Banking Act is essentially a response to the provisions of Islamic law that has become the popular belief in the majority of Indonesian people who crave the realization of banking institutions which are free from usury, which is the Islamic law since his arrival in the archipelago until now classified as living law in the community. This reality is associated with the construction established by von Savigny. Second, the formation of Law No. 21/2008 concerning Islamic Banking is a response to social economic demand both nationally and globally. The presence of Islamic banks have become a necessity in managing the economy and coping with the economic crisis based on the underlying transaction. Third, the Establishment of Law No. 21/2008 concerning Islamic Banking in legal political perspective, has a basic principle, an aim and a response to the dynamic development of Indonesian society, particularly in relation to the development of Islamic economy. Fourth, formation of Islamic Banking Act affects the Islamic economic development in Indonesia, particularly in relation to the development of Islamic banking in Indonesia. Keywords: Sociological Foundation, Islamic Banking Law, Economic Development.